LEVERAGING AI-BASED INTERVENTIONS TO ADDRESS CYBERBULLYING AMONG CHILDREN: A RIGHTS-BASED PERSPECTIVE - Milosevic, Tijana; Verma, Kanishk; Vigil, Samantha; Carter, Michael; Staksrud, Elisabeth; Davis, Brian; O'Higgins Norman, James (AoIR Selected Papers of Internet Research, 2023)
One in three Internet users worldwide are children, and yet children are still insufficiently consulted on Internet governance-related matters as well as with respect to safety design decisions in online environments. Following the adoption of the general comment on the application of UN Convention on the Rights of the Child (UNCRC) in digital environments, this article presents the results of empirical research that solicited children’s input on proposed design of artificial intelligence-based interventions into cyberbullying incidents on popular social media platforms. The article presents the results from interviews and focus groups with 12–17-year-old children from Ireland regarding desirability and effectiveness of proposed interventions; as well as how these affect their rights to safety, privacy and freedom of expression.